Pemilihan Mixing Foundation dengan Teknik Bakar untuk Ketahanan Makeup pada Semua Jenis Kulit - Fahma, Karina Adiba; Wilujeng, Biyan Yesi (Universitas Negeri Surabaya, 2020)
This research was conducted with a burning technique on the selection of a mixing foundation for makeup resistance on all skin types. The purpose of this research is to find out analysis and draw conclusions about the selection of the Mixing Foundation with the combustion technique because this combustion technique is an innovation and not all beauty experts can use this technique in facial makeup. This research method is to collect secondary data in the form of articles or literature review literature type. The results show the conclusions include 1) this burning technique can overcome and reduce the problem of errors in choosing the color of the foundation because the mixing of the foundation can produce the desired color, 2) the results of the mixing foundation with the burning technique provide a long-lasting effect on all skin types 3) It can make the application of products on the face easier, this will be very helpful if you use foundations of various types such as liquid foundations, cream foundations or solid foundations.Keywords: face makeup, Mixing Foundation, burn techniques.